Impact of a risk‐stratified thromboprophylaxis protocol on the incidence of postoperative venous thromboembolism and bleeding. (7th June 2020) - Chahal, R.; Alexander, M.; Yee, K.; Jun, C. M. K.; Dagher, J. G.; Ismail, H.; Riedel, B.; Burbury, K.
Summary: Efforts to reduce postoperative venous thromboembolism are challenging due to heterogeneity in thromboprophylaxis practice. As a result, a 'one‐size‐fits‐all' approach that accounts for surgery‐specific risk, but fails to account for patient‐level variation, is often adopted by healthcare networks. Updated clinical practice guidelines have advocated an individualised risk‐stratified approach that balances the risk:benefit ratio associated with thromboprophylaxis; however, there are limited data confirming effectiveness of these recommendations on the incidence of postoperative venous thromboembolism and bleeding. We developed the surgical‐thrombo‐embolism‐prevention protocol, a novel risk‐stratified algorithm that classified patients into low‐, intermediate‐, and high‐risk profiles according to surgical procedure and patient baseline medical risk. Expert‐endorsed risk‐specific thromboprophylaxis strategies were then applied. A staged quality improvement program was developed to implement the protocol. We postulated that compliance with the protocol would reduce postoperative venous thromboembolism rates without increasing the incidence of postoperative bleeding. Between June 2013 and March 2018, we evaluated the efficacy, safety and sustainability of this risk‐stratified approach in 24, 953 surgical admissions at a dedicated cancer centre. By final implementation, program compliance was 91%. Postoperative venous thromboembolism rates reduced from 3.1 per 1000 surgical admissions to 0.6 per 1000 surgical admissions (relative risk reduction 79%; p < 0.005). Postoperative bleeding rates also declined from 10.0 per 1000 surgical admissions to 6.3 per 1000 surgical admissions (relative risk reduction 37%; p = 0.02). Sustained improvement was evident more than 3 years after implementation. Implementation of the surgical‐thrombo‐embolism‐prevention protocol significantly reduced the incidence of postoperative venous thromboembolism supporting its validation at other institutions. 요약: 수술 후 정맥 혈전색전증을 줄이기 위한 노력은 혈전예방치 료의 다양성으로 인해 어려운 과제이다. 결과적으로, 수술별 위험을 설명하지만 환자 수준의 변동을 설명하지 못하는 '일률 적인' 접근법이 헬스케어 네트워크에 채택되는 경우가 많다. 업데이트된 임상 실무 지침은 혈전예방치료와 관련된 위험 이 익 비율을 균형 있게 조정하는 개별화된 위험 층화 접근법을 지지하였으나 수술 후 정맥혈전색전증 및 출혈 발생에 대한 권고안의 유효성을 확인하는 데이터는 제한적이다. 저자들은 수술 절차와 환자의 기저‐의학적 위험에 따라 환자를 저, 중, 고위험 프로파일로 분류하는 새로운 위험 층화 알고리즘인 수 술‐혈전‐색전‐예방(surgical‐thrombo‐embolism‐preven‐ tion) 프로토콜을 개발하였다. 그런 다음 전문가에 의한 위험 별 혈전예방치료 전략이 적용되었다. 프로토콜 구현을 위해 단계별 품질 개선 프로그램이 개발되었다. 저자들은 프로토콜 을 준수하면 수술 후 출혈 발생률을 높이지 않고 수술 후 정 맥 혈전색전증 비율을 줄일 수 있다고 가정하였다. 2013년 6월 과 2018년 3월 사이에, 저자들은 전용 암 센터의 24, 953개의 외과 입원에서 이 위험 층화된 접근 방식의 유효성, 안전 및 지속 가능성을 평가하였다. 최종 구현시 프로그램 준수율은 91%였다. 수술 후 정맥혈전색전증 발생률은 수술 입원 1000명 당 3.1명에서 수술 입원 1000명당 0.6명으로 감소하였다(상대 적 위험도 감소 79%, p ＜ 0.005). 수술 후 출혈률도 1000회 수술 입원당 10.0명에서 1000회 수술 입원당 6.3명으로 감소하 였다(상대적 위험도 감소 37%, p = 0.02). 지속적인 개선은 구 현 후 3년이 넘도록 그 효과가 분명하였다. 수술‐혈전‐색전 예방 프로토콜의 구현은 수술 후 정맥혈전색전증의 발생률을 크게 감소시키고 다른 기관에 검증을 지지하였다.